SLCO1B1 Gene Polymorphisms (rs2306283 and rs4149056) and Statin-Induced Myopathy in Jordanian Diabetics - Shahrure, Zaineh M.; Irshaid, Yacoub M.; Mustafa, Khader N.; Abujbara, Mousa A.; Al Shhab, Mohammad; El-Khateeb, Mohammed S.; Ajlouni, Kamel M. (Current Reviews in Clinical and Experimental Pharmacology, 2021)
Background: The use of statins to lower high serum cholesterol levels may be associated with a number of adverse reactions, including severe myopathy. The solute carrier organic anion transporter 1B1 (SLCO1B1) gene, which encodes the organic anion-transporting polypeptide OATP1B1, is related to the intracellular transport of statins. The aim of this research was to study the association of rs2306283 and rs4149056 genetic polymorphism of the SLCO1B1 gene with the development of statin-induced myopathy in Jordanian diabetics receiving statins. Methods: We included 413 patients attending the Diabetes Clinics of the National Center for Diabetes, Endocrinology and Genetics, Amman, Jordan. The study was approved by the Institutional Review Board of NCDEG. Myopathy was defined as the elevation of creatine kinase more than 3 times the upper limit of normal. Every subject signed an informed consent form and donated 3-5 mL of venous blood. Genome DNA was extracted from lymphocytes of peripheral blood. Genotypes were identified using the Tetra Amplification Refractory Mutation System of SLCO1B1. Results: The minor allele frequencies of rs2306283 [G] and rs4149056 [C] were 0.38 and 0.23, respectively. The two SNPs followed the Hardy-Weinberg equilibrium. The development of SIM was significantly associated with the homozygous and heterozygous minor allele genotype of rs4149056 (CC and CT), and the homozygous wild type allele genotype of rs2306283 (AA). There was no linkage disequilibrium between the two SNPs in the studied subgroups. Conclusion: Genetic polymorphism in the SLCO1B1 Gene is a risk factor for the development of SIM in Jordanian patients.
Keywords: statins